Sustainable Agriculture for Alaska and the Circumpolar North: Part II. Environmental, Geophysical, Biological and Socioeconomic Challenges - Stevenson, Kalb T.; Rader, Heidi B.; Alessa, Lilian; Kliskey, Andrew D.; Pantoja, Alberto; Clark, Mark; Smeenk, Jeffery (ARCTIC, 2014)
Local agriculture, food security and food supply are limited in Alaska, as well as in much of the circumpolar North. These limitations stem from a suite of challenges that have never been well characterized, categorized, or wholly defined. We identify these challenges as being environmental, geophysical, biological, or socioeconomic in nature, noting that some challenges are interrelated. Additionally, Alaska is expansive, and growing conditions are highly variable across different regions and microclimates of the state. Environmental challenges to Alaskan agriculture are generally linked to high latitude and include strong seasonality, a short growing season, cold temperatures, and unpredictable frosts. Geophysical challenges are characterized by a high percentage of soils that are wet and cold or low in natural fertility. Biological challenges include cultivar adaptability and selection; the control of various pests, weeds, and diseases; and decreased microbial activity in cold soils, which can allow pesticides to linger and slow mineralization of organic fertilizers. Socioeconomic challenges to farming in Alaska are especially limiting and may categorically represent the strongest hindrances to agriculture. They often overlap or interact with many of the identified agro-ecological and biogeographic challenges. Major socioeconomic issues can be a relatively low financial incentive or reward for farmers; inconsistent or limited markets; the high cost of land, infrastructure, and inputs; zoning challenges; a lack of cooperatives; and for rural farmers, time conflicts with more traditional means of subsistence food acquisition. These challenges collectively represent factors that limit agriculture in Alaska, and they provide a basis and justification for developing more sustainable solutions. agriculture; Alaska; challenges; climate; circumpolar; farming; soils; subarctic; sustainable; socioeconomic En Alaska, l’agriculture locale, la sécurité alimentaire et les approvisionnements en vivres sont limités. C’est ...